Protocol for the Process Evaluation of the Online Remote Behavioural Intervention for Tics (ORBIT) randomized controlled trial for children and young people - Khan, K.; Hollis, C.; Hall, C. L.; Davies, E. B.; Mataix-Cols, D.; Andrén, P.; Murphy, T.; Brown, B. J.; Murray, E.; Glazebrook, C. (Current controlled trials in cardiovascular medicine, 2020)
Background Process evaluations are an important component in the interpretation and understanding of outcomes in trials. The Online Remote Behavioural Intervention for Tics (ORBIT) study is a randomized controlled trial evaluating the effectiveness of an Internet-delivered behavioural intervention (called BIP TIC) compared to an Internet-delivered education programme aimed at children and young people with tics. A process evaluation will be undertaken alongside the main trial to determine precisely how the behavioural intervention works and ascertain whether, and if so, how, the intervention could be successfully implemented in standard clinical practice. This protocol paper describes the rationale, aims, and methodology of the ORBIT trial process evaluation. Methods The process evaluation will have a mixed-methods design following the UK Medical Research Council 2015 guidelines, comprising both quantitative and qualitative data collection. This will include analysing data usage of participants in the intervention arm; purposively sampled, semi-structured interviews of parents and children, therapists and supervisors, and referring clinicians of the ORBIT trial, as well as analysis of qualitative comments put into the online therapy platform by participants at the end of treatment. Qualitative data will be analysed thematically. Quantitative and qualitative data will be integrated in a triangulation approach, to provide an understanding of how the intervention works, and what resources are needed for effective implementation, uptake and use in routine clinical care. Discussion This process evaluation will explore the experiences of participants, therapists and supervisors and referring clinicians of a complex online intervention. By contextualising trial efficacy results, this will help understand how and if the intervention worked and what may be required to sustain the implementation of the treatment long term. The findings will also aid in our understanding of factors that can affect the success of complex interventions. This will enable future researchers developing online behavioural interventions for children and young people with mental health and neurological disorders to gain invaluable information from this process evaluation. Trial registration International Standard Randomised Controlled Trials Number, ISRCTN70758207 . Registered on 20 March 2018. ClinicalTrials.gov, NCT03483493. Registered on 30 March 2018.